2001
DOI: 10.1067/mnc.2001.117173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left ventricular endocardial volumes and ejection fractions computed from gated perfusion SPECT with magnetic resonance imaging: Comparison of two methods

Abstract: QGS and ECTb values of cardiac function computed from 8-frame gated perfusion SPECT correlate very well with each other and correlate well with MR. Averaged over all subjects, ECTb measurements of EF are not significantly different from MR values but QGS significantly underestimates the MR values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 10 publications
5
57
2
1
Order By: Relevance
“…Subsequent studies compared the QGS results with other reference techniques, such as equilibrium radionuclide angiocardiography (ERNA), echocardiography, contrast ventriculography and magnetic resonance imaging [16, 19-21, 23, 26-36, 55]. The Emory Cardiac Toolbox (ECTb, Emory University, Atlanta, GA) has also been extensively validated by comparison with first-pass radionuclide ventriculography, ERNA, echocardiography and magnetic resonance imaging [23,25,30,34,55]. Furthermore, comparative studies with ERNA and magnetic resonance imaging have confirmed the reliability of 4D-MSPECT (University of Michigan Medical Center, Ann Arbor, MI) [32,34,55,56].…”
Section: Value Of Gated Spect For Estimating Left Ventricular Functionmentioning
confidence: 99%
“…Subsequent studies compared the QGS results with other reference techniques, such as equilibrium radionuclide angiocardiography (ERNA), echocardiography, contrast ventriculography and magnetic resonance imaging [16, 19-21, 23, 26-36, 55]. The Emory Cardiac Toolbox (ECTb, Emory University, Atlanta, GA) has also been extensively validated by comparison with first-pass radionuclide ventriculography, ERNA, echocardiography and magnetic resonance imaging [23,25,30,34,55]. Furthermore, comparative studies with ERNA and magnetic resonance imaging have confirmed the reliability of 4D-MSPECT (University of Michigan Medical Center, Ann Arbor, MI) [32,34,55,56].…”
Section: Value Of Gated Spect For Estimating Left Ventricular Functionmentioning
confidence: 99%
“…Various modalities, including quantitative echocardiography (ECHO), semiquantitative ECHO, radionuclide ventriculography (RNA), methoxyisobutyl isonitrile scanning, angiography, computed tomography (CT), positron emission tomography and magnetic resonance imaging (MRI), exist for estimating LVEF (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). In clinical practice, ECHO is often used as the first-line test for screening patients for decreased LVEF (17).…”
mentioning
confidence: 99%
“…In which quantitative assessment of end-diastolic and end-systolic perfusion, wall motion and wall thickening using the 20-segment bull's eye representation of the QGS model [ figure 2], as well as estimates for end-diastolic (EDV) and end-systolic (ESV) ventricular volume and derived stroke volume and LVEF is incorporated. The underlying algorithms have been reviewed in literature [2][3][4][5][6][7][8][9][10][11][12][13]17]. The software algorithm implementation is the same in the different camera systems.…”
Section: Gated Spect Protocolmentioning
confidence: 99%
“…With regard to the validation of the Cedars-Sinai's Quantitative SPECT (QGS) software, several requirements have already been met. The algorithm and its basic validation have already been described [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, one particular issue is still not fully solved: reproducibility of the quantitative assessment of regional functional parameters in the presence of severe major defects or artifacts.…”
Section: Introductionmentioning
confidence: 99%